Understanding the Distributional Impacts of Increases in Fuel Prices on Poverty and Inequality in Paraguay - Gustavo J. Canavire Bacarreza; Lyliana Gayoso de Ervin; Juan José Galeano; Juan Pablo Baquero (Institute of Labor Economics (IZA), 2023)
The recent global increases in fuel prices threaten the gains in poverty reduction that countries like Paraguay have achieved over the past few decades. Therefore, policy makers must understand the potential distributional impacts of increases in fuel prices to evaluate the implementation of alternative measures that could mitigate these impacts. This paper analyzes the potential effects of fuel prices on poverty and inequality in Paraguay. Using microsimulation methods and based on the Commitment to Equity framework, it estimates the impact of higher fuel prices on welfare, poverty, and inequality based on three scenarios: (a) increases in gasoline prices, (b) increases in diesel prices, and (c) simultaneous increases in gasoline and diesel prices. The results obtained suggest that the total impact of increasing fuel prices tends to be more regressive in Paraguay. At the same time, the results of the simulations indicate small effects on income inequality.
Keywords: D6; Q4; I3; P36; 330; fuel prices; poverty; inequality; Paraguay